(untitled) (Sains Humanika, 2018)
In order to remain competitive in the global economy, many employers emphasized lifelong learning on their workers. But most of them focused on formal learning and tend to overlook the informal learning in the workplace. Current evidence suggests that informal learning is far more important for skill development and predict employees’ behavior in the workplace. Therefore, this study takes into account the impact of informal workplace learning on employees’ job satisfaction. Samples of the study were 197 property executives. Instruments used in this study were Small Business Workplace Learning Survey (SBWLS) and Job Satisfaction Survey (JSS). Result shows that there was a significant positive impact of informal workplace learning on the job satisfaction. Further analysis concluded that all three components of informal workplace learning such as past episode, current experience and future behavior were positively significant predictors of job satisfaction among property executives. Some limitations and recommendations for future research were discussed in this article. For overall, this study provided full support for the predictive role of informal workplace learning towards employees’ job satisfaction especially in property consulting firms.